France and the Destruction of the Jesuits, 1759-65 : Three Treatises - Maryks, Robert Aleksander, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
The second volume in the Anti-Jesuit Literature series at Brill casts a revealing light on a crucial moment in eighteenth-century France: the suppression of the Jesuits. Through the expert translation of three representative treatises by Jotham Parsons and Patricia M. Ranum, this collection delves into the heart of the conflict, presenting views from Jansenist-Gallican magistrates, conservative clerics, and Enlightenment thinkers. Edited with contextual commentary by Robert A. Maryks and Jotham Parsons, the volume not only navigates the complexities of the Jesuits' decline but also places it in the context of the broader Enlightenment critique, exploring the intricate interplay between evolving ideas of governance, faith, and intellectual freedom.